Experimental investigation of continuous-wave supercontinuum ring laser composed of clad-pumped Er/Yb codoped fiber and highly-nonlinear optical fiber - Lee, Ju Han; Katoh, Kazuhiro; Kikuchi, Kazuro (ELSEVIER SCIENCE BV, 2006)
We experimentally demonstrate a practical benefit of our proposed continuous-wave (CW) supercontinuum (SC) generating ring laser scheme in terms of low-cost device implementation and then investigate its output intensity noise property, as a further study to our previous paper of Ref. [J.H. Lee, Y. Takushima, K. Kikuchi, Opt. Lett. 30 (2005) 2599]. First, we implement a practical and low-cost CW SC laser using a double clad Er/Yb codoped fiber and a highly nonlinear dispersion-shifted fiber (HNL-DSF). Unlike the scheme in Ref. [J.H. Lee, Y. Takushima, K. Kikuchi, Opt. Lett. 30 (2005) 2599] the gain medium of an Er/Yb fiber is clad-pumped by low quality multimode pump LDs to underline the fact that our proposed scheme does not require any high power single-mode laser pump. A SC of a bandwidth larger than 470 nm is readily achieved. Next, we measure relative-intensity-noise (RIN) of the generated SC and compare it with that of a pumped Er/Yb fiber ASE. The SC laser is found to have a much higher RIN than the ASE due to the nonlinear amplification of quantum fluctuations both in the seed light oscillation and in the Raman scattering process. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: DISPERSION-SHIFTED FIBERS; ERBIUM-DOPED FIBER; HIGH-POWER; COHERENCE TOMOGRAPHY; GENERATION; CAVITY